HUBUNGAN GAYA PENGASUHAN AUTORITATIF DENGAN MINAT MEMBACA PADA SISWA SEKOLAH MENENGAH PERTAMA S PSM DI BUKITTINGGI - Refiana Ulfa; Duryati Duryati (Universitas Negeri Padang, 2021)
Abstract: The relantionship between authoritative parenting styles and students reading interest in junior high school students S PSM in Bukittinggi. This studyy aims to determinee the relationship between authoritative parenting styles and students' reading interest in juniorr high school students S PSM in Bukittinggi. This type of research is quantitative, using a correlationall method. The subjects in this study were 60 students starting from class VII-IX in junior high school in Bukittinggi using total sampling technique. The results of this study indicatee the value of r correlaction r table .254>.005, which means that Ha is rejected and Ho is accepted. It can be concluded that in this study, there is no relationship between authoritativee parenting styles and reading interest in junior high school students of PSM in Bukitinggi. PSM junior high school students have a high interest in reading and a high parenting style. Abstrak: Hubungan gaya pengasuhan autoritatif dengan minat membaca siswa pada siswa sekolah menengah pertama S PSM di Bukittinggi. Penelitian ini bertujuan untuk mengetahui hubungan gayaa pengasuhan autoritatif dengan minat membaca siswa pada siswa menengah pertama S PSM di Bukittinggi. Jenis penelitian yaitu kuantitatif dengan menggunakan metodee korelasional. Subjek penelitian ini berjumlah 60 siswa dimulai dari kelas VII-IX di SMP S PSM di Bukitinggi dengan menggunakan teknik total sampling. Pada hasil penelitiann ini menunjukan nilai r tabel > r korelasi = .245 > .005 yang diartikan Ha ditolak dan H0 di terima. Dapat disimpulkan bahwa gaya pengasuhan otoritatif tidak berhubungan dengann minat membaca siswa SMP S PSM di Bukitinggi. Siswa SMP S PSM di Bukitinggii mempunyai minat membaca yang tinggi dan gaya pengasuhan orang tua yang tinggii.